Gambaran Kesiapsiagaan Warga dalam Menghadapi Bencana Tanah Longsor di Dukuh Gesikan Desa Jrakah Selo Boyolali - Putri Wulandari; Irma Mustika Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Landslides are geological disasters that can cause fatalities and large material losses, caused by uneven and unstable soil structures. Objective: To obtain an overview of residents' preparedness in facing landslides in Dukuh Gesikan, Jrakah Selo Boyolali Village. Method: This research uses a descriptive survey method with a sample size of 76 respondents and uses a stratifiet random sampling technique. Results: The results showed that based on the characteristics of the respondents, the majority were in the age range 26-45 years (48.7%), male (56.6%), junior high school education (44.7%). The general results showed that the preparedness of the residents of Dukuh Gesikan, Jrakah Selo Boyolali Village was in the